The putative role of oxidative stress and inflammation in the pathophysiology of sleep dysfunction across neuropsychiatric disorders: focus on chronic fatigue syndrome, bipolar disorder and multiple cclerosis - Morris, Gerwyn (2018)
Sleep and circadian abnormalities are prevalent and burdensome manifestations of diverse neuro-immune diseases, and may aggravate the course of several neuropsychiatric disorders. The underlying pathophysiology of sleep abnormalities across neuropsychiatric disorders remains unclear, and may involve the inter-play of several clinical variables and mechanistic pathways. In this review, we propose a heuristic framework in which reciprocal interactions of immune, oxidative and nitrosative stress, and mitochondrial pathways may drive sleep abnormalities across potentially neuroprogressive disorders. Specifically, it is proposed that systemic inflammation may activate microglial cells and astrocytes in brain regions involved in sleep and circadian regulation. Activated glial cells may secrete pro-inflammatory cytokines (for example, interleukin-1 beta and tumor necrosis factor alpha), nitric oxide and gliotransmitters, which may influence the expression of key circadian regulators (e.g. the CLOCK gene). Furthermore, sleep disruption may further aggravate oxidative and nitrosative, peripheral immune activation, and (neuro) inflammation across these disorders in a vicious pathophysiological loop. This review will focus on chronic fatigue syndrome, bipolar disorder, and multiple sclerosis as exemplars of neuro-immune disorders. We conclude that novel therapeutic targets exploring immune and oxidative & nitrosative pathways (p.e. melatonin and molecular hydrogen) hold promise in alleviating sleep and circadian dysfunction in these disorders.